Parametric Simulation Study of Liquid Film Cooling of Hydrocarbon Liquid Rocket Engine - Huixin Yang; Haoyu Zou; Zeming Song; Wenhao Yu (Aerospace)
The hydrocarbon liquid rocket engine working environment is harsh; the thrust chamber needs to withstand high temperatures and a high-pressure working environment, and the thrust chamber wall material is difficult to bear, so it is necessary to design the cooling structure to reduce the gas damage to the chamber wall. Liquid film cooling is a common cooling method for hydrocarbon rocket engines, and numerical simulation is an important method for studying liquid film cooling. Most of the liquid film cooling numerical simulation is for a fixed model. This paper proposes a liquid film cooling numerical calculation method for a variable-configuration hydrocarbon liquid rocket engine, based on the secondary development of Fluent software (ANSYS Fluent 2022) to form a high-energy hydrocarbon liquid rocket engine design software, which can be realized on the Qt platform. The visualization interface can be for different engine injection port locations, numbers, angles, mass flow rates, and other parameters, to calculate and improve design efficiency and reduce operating difficulty.